Sediment Volume Measuring Tool Using DYP-L04 Type Ultrasonic Sensor Based on Arduino Mega 2560 R3 - Muhammad Rifky Aulia; Sri Arttini Dwi Prasetyowati; Bustanul Arifin; Slamet Imam Wahyudi; Floris Boogaard; Suhartono Suhartono; Raditya Rahmat Wijaya (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Many rivers in Indonesia had very poor water clarity due to a mixture of dirt and mud in the water. Polluted rivers were often found in areas near settlements, where household waste that flowing into rivers made the water look dirty and turbid. Pollutants dissolved in water will bind to small particles and settle at the bottom of the river, due to sedimentation. This research designed a device to detect sediment volume in the rivers. This device used an ultrasonic sensor type DYP-L04 and a rotary encoder for calculating volume, with Arduino Mega 2560 R3 as a processor. There is a PG45 motor that was used to set the motor speed to be constant. This ultrasonic sensor works based on the Arduino programming algorithm that has been designed, so that the device can measure sediment volume optimally. The results of this research showed that the device could determine the volume of sediment with the average error score less than 10 %.